Enhancing dialogue between religious traditions: an Islamic perspective - Bakar, Osman (Amsterdam University Press, 2020)
This chapter provides an overview of Islam's historical experiences in interreligious dialogue through highlights of its 'golden ages' in this particular domain of multicultural societal living within its civilization. It examines these golden ages in interreligious dialogue in three notable geo-cultural and historical settings--Muslim-ruled Spain, Chinese Islam in Ming-ruled China, and Indian Islam under Mughal rule--following an introductory discussion of Muslim exemplary treatment of non-Muslims during the rule of the first four Caliphs succeeding the Prophet Muhammad. On the basis of this discussion the author concludes that it is generally the case that interreligious dialogue and cooperation presents itself as a necessary contributory factor of the Golden Age of all religiously pluralistic societies, especially of Islamic civilization.